2018
DOI: 10.1038/s41467-018-04375-6
|View full text |Cite
|
Sign up to set email alerts
|

Cultural hitchhiking and competition between patrilineal kin groups explain the post-Neolithic Y-chromosome bottleneck

Abstract: In human populations, changes in genetic variation are driven not only by genetic processes, but can also arise from cultural or social changes. An abrupt population bottleneck specific to human males has been inferred across several Old World (Africa, Europe, Asia) populations 5000–7000 BP. Here, bringing together anthropological theory, recent population genomic studies and mathematical models, we propose a sociocultural hypothesis, involving the formation of patrilineal kin groups and intergroup competition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 70 publications
(89 reference statements)
4
51
0
Order By: Relevance
“…Second, we predict an increase in proactive aggression starting in the third stage, and accelerating in the fourth stage, consistent with the considerations of gradual language evolution. There is already some initial evidence for this hypothesis, as collaborative inter-group conflicts became widespread during the Neolithic (Zeng et al, 2018). But further evidence can certainly be sought to better support or falsify this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, we predict an increase in proactive aggression starting in the third stage, and accelerating in the fourth stage, consistent with the considerations of gradual language evolution. There is already some initial evidence for this hypothesis, as collaborative inter-group conflicts became widespread during the Neolithic (Zeng et al, 2018). But further evidence can certainly be sought to better support or falsify this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Socially coordinated violence (proactive aggression) potentially became possible only with the onset of symbolic thought and complex cognition because the same capacities for communication and sociality allow warfare and conflict resolution and avoidance (Kissel and Kim, 2019). In fact, features of self-domestication reached a peak at the end of Upper Paleolithic (Cieri et al, 2014), right before collaborative inter-group conflicts became widespread during the Neolithic, as shown by genetic evidence (Zeng et al, 2018). 3 While it may be true, as pointed out by a reviewer, that derogatory language can be used playfully in an endearing way, this is of course also true of physical aggression, such as hitting.…”
Section: The Language Evolution/ Self-domestication Feedback Loop: a mentioning
confidence: 99%
“…Since the male pool is not structured, the MSY tree has no collecting phase and Ne m remains essentially unchanged beyond 2 kya. In the future, it will be interesting to make a more comprehensive re-evaluation of the relationship between descent rules and Ne m /Ne f ratios across different Bantu populations, since studies in other regions of the world have shown that the more structured sex may not display the highest Ne if the extinction rate of clans is high [43,46].…”
Section: The Influence Of Socio-cultural Behaviors On the Diversity Omentioning
confidence: 99%
“…By identifying mtDNA, Y-chromosomal DNA and nuclear DNA; ancestry, origin and admixture can be ascertained [24][25][26][27] . It has been shown that Yamnaya pastoralists contributed Y chromosome R1a and R1b haplogroups to continental Europe almost entirely replacing the previously wide-spread G2a haplogroup 1,2 .…”
mentioning
confidence: 99%